2013
DOI: 10.1093/nar/gkt057
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic TPP riboswitch regulation of alternative splicing involving long-distance base pairing

Abstract: Thiamin pyrophosphate (TPP) riboswitches are found in organisms from all three domains of life. Examples in bacteria commonly repress gene expression by terminating transcription or by blocking ribosome binding, whereas most eukaryotic TPP riboswitches are predicted to regulate gene expression by modulating RNA splicing. Given the widespread distribution of eukaryotic TPP riboswitches and the diversity of their locations in precursor messenger RNAs (pre-mRNAs), we sought to examine the mechanism of alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 43 publications
1
92
0
1
Order By: Relevance
“…In the fungus Neurospora crassa, TPP binding favors a long-distance (>500 nucleotides distant) base-pairing interaction that loops out internal 5 splice sites, thereby favoring a specific alternative splicing configuration (58). In contrast to the approximately two dozen experimentally validated classes of riboswitches in prokaryotes (9), the TPP riboswitch is the only known eukaryotic riboswitch identified to date, but high-throughput screening for metabolite effects on RNA structuromes may identify eukaryotic RNA sequences that perform as functional riboswitches, perhaps with the involvement of proteins.…”
Section: Meta-properties Relating Rna Structure and Mrna Processingmentioning
confidence: 99%
“…In the fungus Neurospora crassa, TPP binding favors a long-distance (>500 nucleotides distant) base-pairing interaction that loops out internal 5 splice sites, thereby favoring a specific alternative splicing configuration (58). In contrast to the approximately two dozen experimentally validated classes of riboswitches in prokaryotes (9), the TPP riboswitch is the only known eukaryotic riboswitch identified to date, but high-throughput screening for metabolite effects on RNA structuromes may identify eukaryotic RNA sequences that perform as functional riboswitches, perhaps with the involvement of proteins.…”
Section: Meta-properties Relating Rna Structure and Mrna Processingmentioning
confidence: 99%
“…Nevertheless, a novel direction in which MSA-based methods could next develop is the exhaustive genome-wide analysis of short, well-conserved intronic motifs. In the majority of studied cases, the evolutionary constraints were so high that the complementary motifs remained almost unchanged during large evolutionary distances such as, for instance, mammalian radiation (Raker et al 2009;Pervouchine et al 2012;Li and Breaker 2013). Therefore, the computational tools that make use of compensatory base changes, in fact, cannot use this information because mutations in base-paired regions do not occur frequently enough.…”
Section: First Fold or First Align?mentioning
confidence: 99%
“…Recent studies on RSSs in eukaryotic genes revealed widespread occurrence of long-range RRI with diverse functions such as riboswitches (Li and Breaker 2013) and mediators of exon skipping (Lovci et al 2013), mutually exclusive exon choice (Kreahling and Graveley 2005;Yang et al 2011), and other types of alternative splicing events (Raker et al 2009;Pervouchine et al 2012). Many of these structures are located in regions lacking reliable sequence alignments and contain long, ultraconserved stretches of complementary nucleotides, in which the interacting bases can be separated by distances as large as 10 kb.…”
Section: Introductionmentioning
confidence: 99%
“…Another view is that many supposed noncoding transcripts are the result of experimental artifacts, analysis errors, and transcriptional noise (4,99,108). On the one hand, the repertoire of functions for RNA certainly continues to expand, for noncoding RNA transcripts (2,39,40,83,118), for cis-regulatory RNA sequences in messenger RNAs (32,42,44,80,84,92), and for catalytic RNAs (74,90). On the other hand, high-throughput experiments and computational analysis pipelines have been found to suffer from serious systematic artifacts (65,108,132), and RNA biogenesis, like any biochemical process, must have some background level of infidelity (75,99).…”
Section: Introductionmentioning
confidence: 99%